ØªØ·Ø¨ÙŠÙ‚ Ø¥Ø¯Ø§Ø±Ø© Ø§Ù„Ø¬ÙˆØ¯Ø© Ø§Ù„Ø´Ø§Ù…Ù„Ø© ÙÙŠ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¬Ø§Ù…Ø¹ÙŠ: Ø¯Ø±Ø§Ø³Ø© ØØ§Ù„Ø© ÙÙŠ ÙƒÙ„ÙŠØ© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ù…ØÙ…Ø¯ÙŠØ© Ù…Ø§Ù„Ø§Ù†Ø¬ - Shuhub, Lubna Ahmad (ULUL ALBAB Jurnal Studi Islam, 2016)
The success of an institution or university depends on how the leader educates and implements the strategy. Therefore, an education strategy must be developed by university in every nation worldwide. This research aims to know the implementation of TQM on the Faculty of Islamic Study in Muhammadiyah University, Malang, Indonesia, which are Quality standard, TQM implementation strategy, TQM evaluation, the obstacles of TQM implementation in the Faculty of Islamic Study in Muhammadiyah University, Malang. This research employs descriptive analysis. The instrument of data collection is by interviewing, documenting and observing. The most important findings from this research is the quality standard in Muhammadiyah University Malang follows the regulation of National Higher Education and formulated based on KKNI. The strategy of TQM implementation was conducted from the central of quality management, while the process of quality evaluation was conducted directly from the teaching and learning activities. The obstacles faced by the TQM implementation is the lack of professionals and the lack of awareness to implement the new quality standard, and the development of TQM is done by implementing the education policy firmly and it must be controlled continuously.